2022
DOI: 10.3390/electrochem3030038
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transport Limitations in Electrochemical Conversion of CO2 to Formic Acid at High Pressure

Abstract: Mass transport of different species plays a crucial role in electrochemical conversion of CO2 due to the solubility limit of CO2 in aqueous electrolytes. In this study, we investigate the transport of CO2 and other ionic species through the electrolyte and the membrane, and its impact on the scale-up process of HCOO−/HCOOH formation. The mass transport of ions to the electrode and the membrane is modelled at constant current density. The mass transport limitations of CO2 on the formation of HCOO−/HCOOH is inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Creative GDE designs will be of paramount importance to overcome the flooding problem. , Multiscale/multiphysics modeling: CO2R at the electrode is a complex phenomenon that involves multiple phases (gas/liquid/solid) and reactions (homogeneous and heterogeneous), which are affected by the presence of electrolytes and electric field. Advanced modeling of the near-electrode and membrane environment will provide useful insights into the carbonation phenomena that is affected by mass transport, electrochemical and homogeneous reactions, and thermal effects. Moreover, advanced thermodynamic modeling using electrolyte equations of state and molecular simulation are essential for predicting the key thermodynamic, transport, and structural properties of the relevant liquid systems. Such properties are the mutual solubilities (e.g., gases in the aqueous electrolyte phase), transport coefficients (i.e., Maxwell-Stefan and self-diffusivities, ionic conductivities, viscosity), and partial molar properties. Electrolyte-free electrolysis: The presence of electrolytes in CO 2 electrolyzers has several disadvantages. First, liquid products are contaminated with the electrolytes, which complicate the downstream process.…”
Section: Discussionmentioning
confidence: 99%
“…Creative GDE designs will be of paramount importance to overcome the flooding problem. , Multiscale/multiphysics modeling: CO2R at the electrode is a complex phenomenon that involves multiple phases (gas/liquid/solid) and reactions (homogeneous and heterogeneous), which are affected by the presence of electrolytes and electric field. Advanced modeling of the near-electrode and membrane environment will provide useful insights into the carbonation phenomena that is affected by mass transport, electrochemical and homogeneous reactions, and thermal effects. Moreover, advanced thermodynamic modeling using electrolyte equations of state and molecular simulation are essential for predicting the key thermodynamic, transport, and structural properties of the relevant liquid systems. Such properties are the mutual solubilities (e.g., gases in the aqueous electrolyte phase), transport coefficients (i.e., Maxwell-Stefan and self-diffusivities, ionic conductivities, viscosity), and partial molar properties. Electrolyte-free electrolysis: The presence of electrolytes in CO 2 electrolyzers has several disadvantages. First, liquid products are contaminated with the electrolytes, which complicate the downstream process.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the alternative to overcome this limitation that has received greater attention in the literature lies in the supply of a humidified CO 2 stream at the cathode compartment. This way, the use of liquid electrolytes is prevented, since the ion exchange membrane acts as a solid polymer electrolyte. ,,, While the feed of humidified CO 2 improves the mass-transfer in the CO 2 electroreduction process, it also entails higher reactor voltages, making it difficult to operate efficiently at high current densities. Conversely, it has been reported that aqueous electrolytes operate at higher current densities and with lower reactor voltages, but they have associated the mass-transfer limitations due to the low solubility of CO 2 in aqueous electrolytes. , …”
Section: Electrochemical Co2 Reductionmentioning
confidence: 99%
“…However, most of the published works that employed an MEA in a two-compartment electrochemical reactor do not operate at commercially relevant current densities (200 mA·cm –2 ) . The fact that operating at higher current densities is possible when using aqueous electrolytes may promote the search for strategies that enhance the mass-transfer limitations caused by the low solubility of CO 2 in aqueous electrolytes. , In this regard, a novel approach that has recently emerged lies in the application of magnetic fields to improve ERCO 2 (Figure b). The fundamentals of this strategy as well as its reach in the ERCO 2 to formic acid/formate are discussed in the next section.…”
Section: Electrochemical Co2 Reductionmentioning
confidence: 99%
“…The model is validated with experimental data of current density vs. voltage at 1 sun illumination, and the effect of CO 2 flow rate is studied on the current density and efficiency of conversion. Chinnathambi et al [22] investigated the mass transport limitations across the electrolyte and the bipolar membrane for formic acid formation at different pressures, up to 40 bar. Also in this case, the model is validated through experimental data of the current density vs. the applied potential.…”
Section: Introductionmentioning
confidence: 99%